Pengaruh Konservatisme Akuntansi Terhadap Underpricing Saham IPO (Initial Public Offering) - Meri Andani; Salma Taqwa (Universitas Negeri Padang, 2020)
This study examines how the effect of accounting conservatism to IPO’s underpricing and information asymmetry effect the association of accounting conservatism with IPO’s underpricing. The sample of this study using the 97 a-shares companies that went public through IPO’s at both Indonesia Stock Exchage during 2015-2018. Sampling was done by using total sampling method. The type of data used is secondary data obtained from annual report companys and stock price. Based on regression analysis with Eviews9 we find (1) Accounting conservatism has no effect to IPO’s underpricing. (2) Has no effect of high information asymmetry or low information asymmetry on association between accounting conservatism and IPO’s underpricing.